Pengaruh Kompetensi Digital Terhadap Pemahaman Konsep Ipa Siswa Di Smp Negeri 1 Muara Batang Gadis Kelas Viii Tahun Ajaran 2024-2025 - Nurzakiah; Eni Sumanti Nasution; Sri Utami Kholilla Mora Siregar (Universitas Gara Nusantara Padangsidimpuan, 2025)
This study aims to analyze the effect of digital competence on students’ understanding of science concepts (IPA) in Grade VIII at SMP Negeri 1 Muara Batang Gadis for the 2024–2025 academic year. A quasi-experimental method was employed using a nonequivalent pretest-posttest control group design. Two classes were selected as samples, each consisting of 30 students. The experimental class received instruction integrated with digital competencies, while the control class followed a conventional learning approach. The research instruments included a science concept comprehension test and a digital competence questionnaire, analyzed using descriptive and inferential statistics. Results showed that the average posttest score in the experimental class was higher than in the control class, 82.33 versus 72.33, respectively. An independent sample t-test yielded a significance value of 0.000 (<0.05), indicating a significant effect of digital competence on science concept comprehension. It is concluded that the integration of digital competence in science learning significantly enhances students’ understanding of scientific concepts and supports 21st-century skill development.